Knowledge, Attitudes, and Barriers Regarding Health Research among Medical Students in Saudi Arabia - Zafar, Mubashir; Kareem, Abdul; Fawaz, Ali; Fares, Reem; Saad, Wadha (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Research is the basic component of health science curriculum. AIM: The objective of the study is to determine the knowledge, attitude, and barriers regarding health research among health science students. METHODS: It is a cross-sectional study and 294 study participants were selected through stratified random sampling from different health science colleges (medicine, dental, nursing, and applied science). A validated, structured, and pre-tested questionnaire was used. Knowledge and attitudes were determined through scales. Analysis of variance and t-test were applied to determine the mean scores of knowledge and attitude, and multiple regression analysis was used to determine the factors which affect on knowledge and attitude. RESULTS: Knowledge and attitude mean scores were 4.36 ± 2.44 and 2.74 ± 1.17, respectively. Knowledge and attitude were increase significantly with increasing academic year of study in all health science colleges (Regression coefficient 0.043 [p = 0.032] and 0.005 [p = 0.040] for knowledge and attitudes, respectively). Most common barriers for research were lack of proper mentoring from the faculty staff and lack of time due to over burden with educational activities CONCLUSION: Health science students had moderate level of knowledge and attitude toward health research with common barrier which was lack of proper mentoring from the faculty. There is need for address the barrier for research and more integration of curriculum with research which improved the knowledge and attitude level.